Preparation and stabilization of emulsions stabilized by mixed sodium caseinate and soy protein isolate. (October 2015) - Ji, Juan; Zhang, Jianpan; Chen, Jiashu; Wang, Yalong; Dong, Ni; Hu, Chunli; Chen, Hangping; Li, Ge; Pan, Xin; Wu, Chuanbin
Abstract: The purpose of this research was to prepare emulsions stabilized by mixed proteins to achieve excellent storage stability and superior functional properties. The emulsions (O/W) with uniform nanoscale droplets (∼250 nm, polydispersity index < 0.2) were stabilized by mixed sodium caseinate (SC) and soy protein isolate (SPI) and produced through high pressure homogenization. Characteristics of the emulsions were evaluated by Dynamic Light Scattering (DLS), Nanoparticle Tracking Analysis (NTA), Transmission Electron Microscopy (TEM), Rheometer and Turbiscan Lab analyzer. The stabilization mechanism was preliminarily investigated by studying the influences of pH, NaCl and SDS solutions on the droplet size, with the application of sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE). It was found that both flexible protein SC and rigid globular protein SPI were adsorbed on the oil-water interface while some free protein molecules dissolved in the aqueous phase. Electrostatic repulsion and steric stabilization were contributed to the system stability. The retention ratio of vitamin A palmitate was above 93% after three months of storage at room temperature, which demonstrated the protection efficiency of the emulsion was excellent. This work showed a significant promise to develop nutritional products with satisfactory storage stability and physiological benefits. Graphical abstract: Highlights: A nanoscale emulsion with good stability was successfully prepared. Without any other non-nutritional additive, the emulsion size distribution was distinguished homogeneous. Mixed proteins contributed to good stability of the encapsulated liposoluble nutrient. Simple available operations are required to prepare the emulsion.